A novel method for carbon removal and valuable metal recovery by incorporating steam into the reduction-roasting process of spent lithium-ion batteries. (October 2021) - Peng, Qin; Zhu, Xianqing; Li, Jun; Liao, Qiang; Lai, Yiming; Zhang, Liang; Fu, Qian; Zhu, Xun
Graphical abstract: Proposed steam roasting method for valuable metal recovery from spent NCM batteries. Highlights: A steam roasting method was proposed for disposal and recovery of spent LIBs. The carbon removal of spent LIBs was dramatically facilitated by steam. The H2 O only acted on the reaction process of the anode material of spent LIBs. The magnetic recovery efficiencies of Co and Ni after steam roasting were 90% and 93%. Abstract: Oxygen-free roasting could efficiently achieve the recovery of valuable metals from spent lithium-ion batteries (LIBs), but the roasted products have the drawbacks of a high carbon (C) content and a complex separation process. Hence, in this study, a new method incorporating steam (H2 O) into the reduction-roasting recovery process of spent LIBs (steam roasting) was proposed to realize carbon removal and valuable metal recovery simultaneously. The influence of steam on the reduction-roasting process of spent LiNi0.6 Co0.2 Mn0.2 O2 batteries (NCM) was investigated through experimental methods and thermodynamic analysis. The results indicated that the addition of steam could dramatically facilitate the decomposition and reduction process of spent NCM, and the carbon removal efficiency could reach 84%. H2 O only acted on the reaction process of the anode material, and the main component C could be efficiently gasified by steam to produce hydrogen (H2 ) and carbon monoxide (CO), which could significantly accelerate the reduction process of CoO and NiO. The optimal conditions for valuable metal recovery and carbon removal were a H2 O/C mole ratio of 5:1 and a reduction-roasting temperature of 1123 K. After steam roasting, the magnetic recovery efficiencies of Co and Ni were as high as 90% and 93%, respectively. The final recovery products were Co, Ni, and Li2 CO3 with high purities. Therefore, this study is expected to provide a novel approach to achieve efficient disposal and recovery of metals from spent LIBs.